The psychology of coaching, mentoring and learning - Law, Ho (Wiley Blackwell, 2014)
The Psychology of Coaching, Mentoring and Learning addresses the psychological principles upon which organizational and industrial coaching and mentoring is based. The new edition of this text is updatd with new research, taking into account the growth of positive psychology and its role in coaching and mentoring. This book is ideal for coaches, mentors, trainers, psychologists, senior executives, managers, and students with an interest in this field.